Understanding the latest wave and future shape of regional trade and cooperation agreements in Asia - Biswanath Bhattacharyay (Center for Economic Studies and ifo Institute (CESifo), 2006)
Asia accounts for more than 30% of world GDP and contributes half of the global growth in recent years. Despite high growth rates, Asia is still facing considerable socio-economic challenges. If Asia is to reemerge as a major power in the global economy and in order for the region to successfully address its own challenges and issues there is a need to make the region's economies more integrated regionally and internationally. Following the recent global trend, Asia witnessed a wave of subregional and bilateral trade agreements. This paper analyzes the recent trends and patterns and nature of regional trade and cooperation agreements (RTCAs) in Asia and associated problems and prospects. It also attempts to understand the latest wave and the future shape of RTCAs and examines if these RTCAs provide the basis for a new Asia-wide cooperation or for the emergence of new regional trade in blocs of several subregional groupings.
Keywords: F1; F2; Q1; Q4; R4; 330